Diversity Amongst New Zealand Early Childhood Educators - Sue Cherrington; Mary Jane Shuker (New Zealand Journal of Teachers' Work)
The diversity of service types and range of organisations involved in early childhood education (ECE) in New Zealand is a hallmark of the sector, recognised by both the sector and government as a strength in offering choice to families. However, little attention has been paid to issues of diversity within individual early childhood services. This article reports data from a national survey carried out as part of a larger project, The Diversity of Diversity in Early Childhood Education, focusing specifically on educators involved in New Zealand ECE services. The article considers the implications of these results for practitioners, early childhood services, and providers of initial teacher education and professional development programmes for practitioners.